Choosing wisely first line immunotherapy in non-small cell lung cancer (NSCLC): what to add and what to leave out. (May 2019) - Proto, C.; Ferrara, R.; Signorelli, D.; Lo Russo, G.; Galli, G.; Imbimbo, M.; Prelaj, A.; Zilembo, N.; Ganzinelli, M.; Pallavicini, L.M.; De Simone, I.; Colombo, M.P.; et al.
Highlights: Currently, only patients with PD-L1 TPS ≥ 50% can receive immunotherapy (pembrolizumab) as first line treatment in clinical practice and they account for a maximum of 30% of all advanced NSCLC patients. Several phase III studies demonstrated a survival advantage combining immunotherapy to chemotherapy. An open issue is how to choose the most correct therapeutic strategy and to properly select patients for the different available treatment options. To date, PD-L1 expression by immunohistochemistry (IHC) is the only approved marker to select patients for immunotherapy but other factors, for example TMB, are under evaluation. Abstract: Immunotherapy has dramatically changed the therapeutic scenario in treatment naïve advanced non-small cell lung cancer (NSCLC). While single agent pembrolizumab has become the standard therapy in patients with PD-L1 expression on tumor cells ≥ 50%, the combination of pembrolizumab or atezolizumab and platinum-based chemotherapy has emerged as an effective first line treatment regardless of PD-L1 expression both in squamous and non-squamous NSCLC without oncogenic drivers. Furthermore, double immune checkpoint inhibition has shown promising results in treatment naïve patients with high tumor mutational burden (TMB). Of note, the presence of both negative PD-L1 expression and low TMB may identify a subgroup of patients who has little benefit from immunotherapy combinations and for whom the best treatment option may still be platinum-based chemotherapy. To date, first-line single agent immune checkpoint blockade has demonstrated limited activity in EGFR mutated NSCLC and the combination of immunotherapy and targeted agents has raised safety concerns in both EGFR and ALK positive NSCLC patients. Finally, in EGFR mutated or ALK rearranged NSCLC, atezolizumab in combination with platinum-based chemotherapy and bevacizumab is emerging as a potential treatment option upon progression to first line tyrosine kinase inhibitors.